Desain dan Analisa Mesin Pencacah Nilam Dengan Kapasitas 200 Kg/Jam - Miswan, Miswan; Salimin, Salimin; Endriatno, Nanang (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
The Southeast Sulawesi region, which is the East Kolaka area, especially the AERE sub- district, AERE village is an area whose livelihood is in agriculture. One of them is patchouli farming.  In  processing  patchouli,  most  still  use  traditional  methods.  This  makes  the patchouli processing process less efficient, so researchers want to create a tool that can make patchouli processing to save costs. Patchouli chopping machine is an important tool  in  improving  the  observation  of  patchouli  farming.  The  working  principle  of  this machine utilizes the power of a gasoline motor. Through the Puly mechanism and the V- belt produced by the gasoline motor, it will be transferred to the shaft which is connected to the blade. The stages of design and calculation on the patchouli chopping machine consist of calculating the design power, calculating the shaft, calculating the shear stress, torsional  moment  of  the  plan,  designing  the  blade  by  taking  into  account  the characteristic data of patchouli, the average patchouli volume and patchouli mass (ms). . Based on the results of the calculation of the characteristics of the patchouli plant with an average height of patchouli 150 cm, diameter of the main stem 12.79 mm and density of 0.112 g cm, it can be concluded that the power of the gasoline motor used is 6.5 hp with a shaft rotation of n1 3600 rpm , the design power obtained on the shaft design of the  patchouli  chopping  machine  is  9.554  (kw),  the  shear  stress  on  the  shaft  is  1.646 kg/mm², the compressive strength of the slicing knife is 36.2044512 N, with a shear stress of 0.1153008 N/mm².Keywords: Design, analysis, crusher machine,patchouli